The Cultural Aspects and Literary Value of a Text: A Study on Enthaiyum Thaayum - Gayathree, S. (University of Jaffna, 2019)
Translation is the replacement of a piece from one language to another with the emphasis on the linguistic and the semantic aspects of translation. The notion meaning has been argued whether it is semantic or pragmatic or social and all these are combined under ‘cultural aspects’ of translation. Culture plays an extensive role in the process as well as the product of translation. The success of a translation depends upon making the readers to read the original by giving a complete picture of the original with the preservation of the style and manner and all the ease of the original. Literary translation which deals with the sense, feelings and aspiration of people could be possible only by an efficient literary personality. Translation is one of the factors defining cultural sustainability and reshaping the translators especially the literary translators, as human capitals may lead to a better future. This study focuses on ‘The Land of Our Parents’, the translation of ‘ve;ijAk; jhAk;’(EntaiyumTayum) which portrays the fragmentation of the nuclear family in Jaffna due to the Eezham war. The original play ‘ve;ijAk; jhAk;’ (EntaiyumTayum) and the translation ‘The Land of Our Parents’ are the primary sources for this study.The cultural aspects and literary value of the translation is viewed through the parameters of systemic functional approach. Six parameters of systemic functional approach are taken into consideration to see the strategies utilized by the translator with regard to the cultural aspects and literary values of the piece. Through descriptive methodology every parameter is exemplified and elucidated.This may be helpful to reshape the budding translators as human capitals to have a better future.
Keywords: Literary Translation; Systemic Functional Approach; Adequacy; Acceptability